Pengaruh Gaya Kepemimpinan Transformasional dan Motivasi Kerja terhadap Kinerja Karyawan - Yanuariadi Kusuma Baskoro; Yudi Yudi; Irwansyah Irwansyah (Universitas Lambung Mangkurat, 2015)
This study aims to determine the effect of transformational leadership style (7 items) as an exogenous variable / free, work motivation (3 items) and Employee Performance (3 items) as an endogenous variable / tied to the Vocational School (SMK) Telekomunikasi Sandhy Putra Banjarbaru South Kalimantan.The study uses a quantitative approach with a population of 63 people , taken a sample of 58 people . In this study used a questionnaire to reveal the variables that influence the decision of the respondent . Instruments of each item statement was measured using a Likert scale of measurement that uses an interval scale 1-5. Point 1 to 5 are level scores for each statement . The results of the questionnaire first tested the validity and reliability. Further analysis conducted inferential statistics that aims to test the influence of transformational leadership style variable ( X1 ), work motivation ( X2 ) on the performance of the employee ( Y ) as well as to test the hypotheses that have been formulated in this study . This study used path analysis method to examine the contribution that each pathway is indicated by the coefficient of the path diagram of causal relationships between variables X1, X2 on Y. correlation and regression analysis which is the basis of the calculation of the path coefficients. In the calculations using the tools of SPSS for Windows version 21.The results showed that transformational leadership style variable to variable indirectly affect work motivation, work motivation variables directly influence employee performance variables. transformational leadership style variable to variable indirectly affect employee performance, transformational leadership style independent variable has no direct effect on employee performance through workplace motivation.Keywords: Leadership, motivation and performance